Science, technology development and threat to human rights: a need to reformulate legal foundations. (1st January 2013) - Srivastava, S.P.
New technological developments and economic conditions are creating new forms of social behaviour that are fundamentally altering the way we know the world. It appears technology is racing out of legal control. It is a phase where a major part of society is trying to overcome with techno-virus, which has paralysed the autonomy of society. Here, people are looking towards legal system and laws for remedy. The conflict we face today is more a question of the extent to which law or government should or should not influence scientific progress and objectivity of scientific principles. This paper is an attempt to analyse the role of science technology in the development of society. This article has sought to understand whether our legal institutions effectively control technology or not. It is also an attempt to find out the solution for the gap between technology and human rights principles.